The blame game: analyzing gender bias in Danish local elections. (3rd April 2019) - Kjaer, Ulrik; Krook, Mona Lena
ABSTRACT: Diagnosing women's under-representation in electoral politics often involves a "blame game, " seeking to identify the primary factor responsible for depressing the share of women among candidates as well as elected officials. The Danish electoral system – in which parties present ordered lists of candidates but voters have the option to cast preference votes that can rearrange the list order – provides an opportunity to assess the relative role of elite versus voter bias in shaping women's electoral fortunes. Using data from local elections in 2009, we find greater evidence for elite bias against women. We also observe, however, that voters do not widely exploit their preference votes. In an original post-election survey, we discover that "candidate gender" is less important for male and female voters than a host of other characteristics when deciding for which candidate to cast a preference vote.